Developing a Hybrid Training Curriculum for the Inaugural World Health Organization (WHO) Singapore Emergency Medical Team (SGEMT) Using Andragogical Principles for Adult Training - Shu Fang Ho; Joy Li Juan Quah; Doreen Tan; Fadhilah Ishami Muhammad Faisal; Kee Chong Ng (ASEAN Journal of Disaster Health Management (AJDHM), 2025)
Introduction: The WHO-EMT initiative seeks to “enhance surge capacity of countries through promotion of rapid mobilization and efficient coordination of both national and international medical teams and the health-care workforce to reduce loss of life and prevent long-term disability caused by disasters, outbreaks and other emergencies. It values “inclusiveness, transparency, global cohesion and regional adaptation, needs driven and adherence to quality standards and methodology. In partnership with the Ministry of Health (MOH) of Singapore, Singapore Health Services (SingHealth) was tasked to help set up Singapore’s inaugural World Health Organisation (WHO) Emergency Medical Team (EMT) – Singapore Emergency Medical Team (SGEMT). Singapore will be the third ASEAN country, after Thailand & Malaysia, to set up such a WHO EMT programme. SGEMT plans to be verified by WHO by 2024. Methods: Our SGEMT is a Type 1 Fixed EMT and will attend to outpatient and emergency patients in the community over a 14-day overseas deployment, and comprises an 18-member medical team with 5 doctors, 10 nurses, 1 rehabilitative physiotherapist, 1 clinical psychologist and 1 clinical support staff. The medical team are volunteers from all across our SingHealth cluster. In addition to this 18-member medical component, there is an additional 15 member administrative and logistic team from MOH and our designated logistics partner. Our SGEMT therefore comprises 33 members – 18 medical team members and 15 admin / logistics members. In order to adequately prepare all our SGEMT volunteers for deployment, our SingHealth team together with MOH developed a comprehensive and uniquely tailored training programme. The design of this training programme is based on well-established andragogical principles and applications to ensure effective adult learning. Results: All SGEMT volunteers will undergo a three-component hybrid training programme comprising of 1) E-Learning Modules, 2) Face-to-Face Workshop & Table-Top Exercise (TTX) and 3) Ground Deployment Exercise (GDX). Component 2 and 3 aim to help participants consolidate the knowledge acquired in the e-learning component, provide hands-on opportunity to demonstrate both the clinical and non-clinical skills required of SGEMT volunteers. The final integration will first be done via TTX, followed by GDX. Conclusion: The training curriculum and andragogy adopted for SGEMT was to ensure effective adult learning, such that our SGEMT can function seamlessly on the ground once deployed by MOH & WHO.